Effects of microRNA-374 on proliferation, migration, invasion, and apoptosis of human SCC cells by targeting Gadd45a through P53 signaling pathway. Issue 4 (4th August 2017) - Li, Xiao-Jing; Li, Zhi-Feng; Wang, Jiu-Jiang; Han, Zhao; Liu, Zhao; Liu, Bao-Guo
Abstract : The present study investigated the effects of microRNA-374 (miR-374) on human squamous cell carcinoma (SCC) cell proliferation, migration, invasion, and apoptosis through P53 signaling pathway by targeting growth arrest and DNA-damage-inducible protein 45 α (Gadd45a). Skin samples were collected from patients with skin SCC and normal skin samples. Expression of miR-374, Gadd45a, P53, P73, P16, c-myc, bcl-2, Bax, caspase-3, and caspase-9 were detected using quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting. A431 and SCL-1 cells were divided into blank, negative control (NC), miR-374 mimics, miR374 inhibitors, siRNA–Gadd45a, and miR-374 inhibitors + siRNA–Gadd45a groups. Their proliferation, migration, invasion, cell cycle, and apoptosis were evaluated by 3-[4, 5-dimethylthiazol-2-yl]-2, 5 diphenyl tetrazolium bromide (MTT) assay, scratch test, Transwell assay, and flow cytometry. SCC skin tissues exhibited decreased expression of miR-374, P73, P16, Bax caspase-3 and caspase-9, and increased levels of Gadd45a, P53, c-myc, and Bcl-2 compared with the normal skin tissues. The miR-374 inhibitors group exhibited decreased expression of miR-374, P73, P16, Bax caspase-3 and caspase-9, and increased expression of Gadd45a, P53, c-myc, and Bcl-2, enhanced cell proliferation, migration, and invasion, and reduced apoptosis compared with the blank and NC groups; the miR-374 mimics group followed opposite trends. Compared with the blank and NC groups, the miR-374 inhibitors + siRNA–Gadd45a group showed decreased miR-374 level; the siRNA–Gadd45a group showed elevated levels of P73, P16, Bax, caspase-3 and caspase-9, decreased levels of Gadd45a, P53, c-myc, and Bcl-2, reduced cell proliferation, migration, and invasion, and accelerated apoptosis. miR-374 induces apoptosis and inhibits proliferation, migration, and invasion of SCC cells through P53 signaling pathway by down-regulating Gadd45a.